Ratio C-Reactive Protein Terhadap Albumin Dalam Memprediksi Lauren Rumah Sakit Dan Jangka Panjang Pasien STEMI Dengan Infeksi SARS-CoV2 Yang Menjalani Terapi Fibrinolitik - Prana Jagannatha, Gusti Ngurah; Rina Artha, I Made Junior; Surya Pradnyana, I Wayan Agus; Kamardi, Stanly; Kosasih, Anastasya Maria (The Indonesian Heart Association, 2022)
Background: The choice of reperfusion therapy in STEMI patients with COVID-19 is unclear. CRP to Albumin ratio (CAR) found to be a predictor of thrombus burden. This study was to determine the relationship and predictive value of CAR to in-hospital and long-term outcome of STEMI patients with COVID-19 treated with fibrinolytic. Methods: 297 COVID-19 patients with STEMI underwent fibrinolytic were enrolled. In-hospital outcomes were in-hospital mortality due to cardiovascular death which was divided into mortality <48 hours and >48 hours, fibrinolytic failure, and cardiogenic shock. The presence of reinfarction post fibrinolytic and mortality after the patient discharged was assessed as the long-term outcome. Results: During follow-up, 19.8% experienced in-hospital mortality and 16.1% had reinfarction. In the in-hospital outcome, patients with in-hospital death, failed fibrinolytic and cardiogenic shock had higher CAR (6.7+2.4 vs 4.7+1.9; 6.3+1.9 vs 2.1+1.6; 5.5+2.1vs1.8+1.5) with all p-value <0.05. CAR with an optimal cut-off >4.46 can be a predictor of fibrinolytic failure with sensitivity of 86.7% and specificity of 93.6% (PR19.82; 95%CI 10.32-38.06) and predictor of in-hospital death <48 hours with sensitivity of 84.6% and specificity of 82.7% (PR5.02; 95%CI 3.20-7.90). In the long-term outcome, patients who experienced reinfarction and out-hospital death had higher CAR (5.1+1.2vs2.5+2.4; 5.2+1.3vs2.6+2.4) than those who did not experience the event respectively with all p-value <0.05. CAR with an optimal cut-off >3.67 can be predictor of reinfarction with sensitivity of 87.5% and specificity of 73.5% (PR12.250; 95%CI 5.38-27.87). The Cox regression model showing CAR >3.67 was also associated with higher reinfarction event (p=0.001). Conclusion: CAR has the potential to be a predictor of in-hospital and long-term outcomes for STEMI patients with COVID-19 which can help determine which patients need more invasive strategy to prevent mortality and morbidity. This article has a related Erratum.